KAYKOVUSNING “QOBUSNOMA” ASARINING PEDAGOGIK FIKR TARAQQIYOTIDAGI TUTGAN O‘RNI - Nishonov, M.S.; Tumanov, U.F. (SCIENCE and SOCIETY, 2025)
The article analyzes the pedagogical features of Kaykovus's "Qobusnoma" in child rearing, including the pedagogical conditions of education, the translation of the work into different languages, the importance of respecting parents, eloquence, knowledge and intelligence, acquiring scientific knowledge, art, learning war, trade, farming and crafts, observing the rules of etiquette, raising children, generosity and youth.
Keywords: value; ritual; tradition; speaker; upbringing; pedagogical conditions; generosity; nobility